High cryptic diversity in the kleptoparasitic genus Hyalorisia Dall, 1889 (Littorinimorpha: Capulidae) with the description of nine new species from the Indo-West Pacific. (18th September 2020) - Fassio, Giulia; Russini, Valeria; Buge, Barbara; Schiaparelli, Stefano; Modica, Maria Vittoria; Bouchet, Philippe; Oliverio, Marco
ABSTRACT: Species in the family Capulidae (Littorinimorpha: Capuloidea) display a wide range of shell morphologies. Several species are known to live in association with other benthic invertebrates—mostly bivalves and sabellid worms, but also other gastropods—and are believed to be kleptoparasitic filter feeders that take advantage of the water current produced by the host. This peculiar trophic ecology, implying a sedentary lifestyle, has resulted in highly convergent shell forms. This is particularly true for the genus Hyalorisia Dall, 1889, which occurs in deep water in the Caribbean and Indo-West Pacific provinces, with two nominal species recognized so far. Combining morphological, ecological and molecular data, we assessed the diversity of the genus, its phylogenetic position inside the family and its association with its bivalve host, the genus Propeamussium de Gregorio, 1884 (Pectinoidea), resulting in the description of nine new cryptic species. When sympatric, species of Hyalorisia are associated with different host species, but the same species of Propeamussium may be the host of several allopatric species of Hyalorisia .